Descrição de duas novas espécies de bagrinhos do gênero Microcambeva Costa & Bockmann 1994 (Siluriformes: Trichomycteridae) de bacias costeiras do sudeste da Mata Atlântica - Medeiros, Lucas Silva de (2020)
Represented by six species, the genus Microcambeva comprises small psamophilic catfishes endemics of costal basins of Antlantic forest, southeastern Brazil, occurring from north of Paraná state until to south extreme of Bahia state. Recent samplings listed new records of the genus in median portions in Doce river basin, states of Minas Gerais and Espírito Santo, and in Guapi-Macacu river basin, in state of Rio de Janeiro, represents a new species. A new specie, Microcambeva sp. n. “Doce” easily diagnosed from all congeners for nasal, maxillary and rictal barbells medium in size and by the cephalic staining pattern a heart. Distinguish from M. ribeirae and M. filamentosa, except of species “Clade M. draco” for presenting ossification in anterior poriton of autopalatine. Differ, M. barbata¸ except de M. mucuriensis, M. jucuensis and M. draco for presenting ossification on autopaletine rudimentary. Differ of M. mucuriensis and M. draco, except M. jucuensis for anterior process of opercle forked. Distinguish from M. jucuensis for nine odontodes opercle. Microcambeva sp. n. “Guanabara” easily diagnosed from other species, except M. ribeirae and M. filamentosa for absence ossification on anterior portion of autopalatine and fusion of supraorbital pore s6, in central portion of head. Distinguish from all species, excepted M. ribeirae, pectoral din ray not modified in filament, in all species the first ray may change to 5%-80%. Microcambeva sp. n. “Guanabara” differs M. filamentosa for eight odontodes in opercular and interocular patch. The new species differs from M. ribeirae for a rictal barbell elongated, reaching anterior portion of interopercular patch, origin of anal fin verticality in 19th vertebra and a patterns color formed for dark chromatophores in median of trunk.